Physical properties of 1-D ZnO-based nanostructures - Pang, Christina Ai Lin (2009)
Nanotechnology refers to the design, synthesis and applications of nanostructures and nanomaterials. When a structure undergoes miniaturisation to the nanometre scale, it may start exhibiting new physical properties or phenomena.